Moral Value and Character Education Found in Movie Miracle in Cell No 7 - Nikie Sulayani; Listra Sitohang; Linsay Oktati Simbolon; Merry Susanty Br Tarigan (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Moral values are values that relate to a person's good or bad, this moral value is also the content of character education. This study aims to determine the moral values and characters of the miracle cell film no.7. The researcher chose this film because this film really displays good moral values and characters. The study was the conducted by applying quantitative data with qualitative results as the findings. The data was alayzed by the moral value and character theory proposed by Bollen ( sacrifice, mutual help, love and affection, keeping promise, upholding justice, dedicated) and the character education (honesty, never give up, returning the favour, independence, responsibility, friendship, curiosity). After analzing the data, the researchers found that the movie performed all types of  moral value such as is, sacrifice, mutual help, love and affection, keeping promises, justice, devoted with the character of, honesty, never give up, return, fair attitude, independent, responsibility, friendship, and curiosity. Therefore, the researchers concludes that it is deeply recommended to watch since it really shows the good moral value for audience or students especially to act in daily life.